A Movement-Efficient Deployment Scheme Based on Information Coverage for Mobile Sensor Networks. (3rd December 2015) - Cheng, Wei; Li, Yong; Jiang, Yi; Yin, Xipeng
Abstract : Covering the surveillance region is a key task for wireless sensor networks. For mobile sensors, the deployment of sensors at appropriate locations is the key issue for sufficient coverage of surveillance area, and efficient resource management of sensor network. Previous studies most utilize physical coverage model for developing deployment schemes, in that the sensor resources may be wasted during the deployment for coverage. In this paper, a novel movement-efficient deployment scheme for mobile sensor networks is proposed, which adapts the information coverage model and the classical potential field method. The performances of the proposed scheme are evaluated comparing to two other schemes in aspects of coverage rate, coverage hole rate, ideal moving distance, and actual moving distance through extensive simulations. Simulation results show that the proposed scheme performs better than these related schemes in both coverage and movement efficiency.